2, 4-Ditellurouracil and its 5-fluoro derivative: Theoretical investigations of structural, energetics and ADME parameters. (June 2017) - Alswaidan, Ibrahim A.; Sooknah, Kritish; Rhyman, Lydia; Parlak, Cemal; Ndinteh, Derek T.; Elzagheid, Mohamed I.; Ramasami, Ponnadurai
Graphical abstract: Highlights: Tautomers of 2, 4-ditellurouracil and 5-fluorotellurouracil were studied using DFT method. The keto-enol tautomerism was studied in the gas phase. The diketo form is the most stable tautomer. Substitution of hydrogen by fluorine causes a decrease in the interconversion barriers. The ADME parameters of the most stable diketo and dienol tautomers were predicted. Abstract: 2, 4-Ditellurouracil exhibits keto-enol tautomerism via different pathways resulting in seven tautomers. These pathways were studied in the gas phase using density functional theory method. The functionals used were BLYP, B3LYP and BHLYP and the basis sets were 6–311++G(d, p) for all atoms except that LanL2DZ ECP was used for tellurium atom only. The results indicate that the diketo form is more stable as observed for uracil and its sulfur and selenium analogues. The effect of introducing fluorine at position 5 was also investigated and the energy difference between the diketo and dienol forms is reduced. 2, 4-Ditellurouracil and its 5-fluoro analogue are expected to exist exclusively as the diketo form due to the high interconversion energy barrier. We extended the investigation to predict ADME parameters of the most stable diketo and dienol tautomers in view of understanding their biological properties. This research enlightens keto-enol tautomerism of 2, 4-ditellurouracil and its 5-fluoro derivative with additional insights to biological functions.